Capas das revistas Veja e Época, cenas da enunciação e persuasão: uma análise verbo-visual - Pagani, Maria Fernanda de Castro Andrade (2017)
This paper deals with journalistic discourse with the objective of analyzing how effects of meaning are produced by the relationship between verbal and visual languages. For the accomplishment of this work, covers of magazines Veja and Época, published in the printed media, analyzed from the central concept of scenes of the enunciation, in dialogue with the notion of ethos, based on the works of Dominique Maingueneau. The conception of language adopted as the basis of the analytical procedures is the one that privileges the observation of linguistic and non linguistic elements in constant intermediation and implication - language, discourse, history, in complex relation -, around the production and transmission of meanings. As the result of this paper made it possible to understand how the expressive use of linguistic elements and visual elements was established in different strategies to persuade the reader and direct meanings in their understanding of the layers.